2020
DOI: 10.3389/fpsyg.2020.01541
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Relation Between Self-Compassion and Suicide Risk Among Adolescents in a Post-disaster Context: Mediating Roles of Gratitude and Posttraumatic Stress Disorder

Abstract: Background The suicide risk among adolescents post-earthquake remains an important issue in trauma psychology. While existing studies and theories suggest that factors such as self-compassion, gratitude, and posttraumatic stress disorder (PTSD) play roles in the risk of suicide, few studies have combined these factors to explore the relationship between them. Objective This study examined the mediating roles of gratitude and PTSD in the relationship between self-compass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 82 publications
5
20
0
Order By: Relevance
“…Several studies have demonstrated that elevated psychological distress was commonly observed following disasters (Jafari et al, 2020;Liu et al, 2020). The major mental health symptoms that impacted post-burn distress including depression or anxiety have been found to have a significant correlation with suicide (Johnson et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have demonstrated that elevated psychological distress was commonly observed following disasters (Jafari et al, 2020;Liu et al, 2020). The major mental health symptoms that impacted post-burn distress including depression or anxiety have been found to have a significant correlation with suicide (Johnson et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated that psychological distress was likely to occur in the wake of disaster experiences (Jafari et al, 2020;Paton, 2019). Both pre-disaster psychological conditions and post-disaster variables have been identified as one of the predictors of health problems after disasters, however, post-disaster stress may have more impact on the mental well-being of survivors (Liu et al, 2020;Math et al, 2015). Moreover, post-disaster stress and its associated mental health problems were shown to be attributable to suicidal behaviors (Jafari et al, 2020).…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…The scale contains seven aspects of problems, including violent behavior, suicidal ideation, and sleep problems. Three items are used to assess violence (e.g., “violent conflict with others” and “quarrel with others”) and three items are used to assess suicidal ideation (e.g., “thoughts of suicide” and “preparing for suicide”) (Liu et al, 2020). The Cronbach’s α was 0.77 for violent behavior and was 0.90 for suicidal ideation of all students.…”
Section: Methodsmentioning
confidence: 99%
“…As a major traumatic event, earthquakes seriously threaten the safety of people. Research has also revealed that earthquakes not only impair people's mental health but also cause them to develop maladaptive behavior patterns, such as substance abuse, self-harm, and suicide (Liu et al, 2020; Pollice et al, 2011).…”
Section: Self-compassion Affects Nssimentioning
confidence: 99%
“…As self-attitude makes people experience painful emotions after trauma, NSC amplifies negative emotions and cognition, thereby utilizing multiple cognitive resources, which may not be conducive to feeling complete gratitude when they receive help from others. In a study on the effects of earthquakes on adolescents, PSC was found to considerably increase their gratitude levels, and NSC exhibited a negative effect on gratitude (Liu et al, 2020).…”
Section: Self-compassion Affects Nssimentioning
confidence: 99%